Manfaat Penambahan Tiang Jaringan Guna Meningkatkan Komunikasi Digital di Jl. H.M. Yamin Kel. Sidodadi Kec.Medan Timur - Br Nasution, Najiah Maisaro; Siregar, Susilawati; Humaidi, Samir; Zidansyah, Arif; Simamora, Irma Yusriani (Da'watuna: Journal of Communication and Islamic Broadcasting, 2023)
Information technology is the latest long wave of the socio-economic evolution of mankind by bringing changes in all lines of human life, including social, economic and political. The birth of digital communication has brought changes in people's behavior, including shifts in culture, ethics and existing norms. Research on information technology and social change has progressed significantly, ranging from speculative studies of its potential impact on social and economic life to detailed analysis of digital communications[1]. The discussion of digital communications and social change is part of the wider literature on innovation theory that began with Shannon's "digital" conceptualization in 1948. And this is very influential whether or not the internet network. Therefore, additional network poles were carried out to facilitate the telecommunication network on Jl. HM Yamin. This work was carried out by PT. Fiber. The results discussed in this study are the addition of network poles carried out by PT. Fiber Network on Jl. H.M Yamin and its benefits for digital communication. This study uses qualitative methods, using a descriptive approach. In the process of qualitative research the emphasis is on the views of the subject and the theoretical basis used by the researcher as a guide, so that the research process is in accordance with the facts found in the field when conducting research. Keywords: network pole, digital communication